Experimental insights into catalytic oxidation of 1,6-hexanediol to ε-caprolactone over (p-cymene)RuCl2(L) complexes in non-polar media - Pratya Promchana; Kittisak Choojun; Nararak Leesakul; Saowanit Saithong; Kittipong Chainok; Tawan Sooknoi (Reaction Chemistry & Engineering, 2022)
The activity-pocket site dimension ( θ c ) dependence of ( p -cymene)RuCl 2 (L) supports associative interchange mechanism for 1,6-hexandiol oxidation to ε-caprolactone. Methyl isobutyl carbinol, a H-accepting product, reacts with Ru, causing deactivation.
Keywords: Asymmetric Hydrogenation and Catalysis; Metal-Catalyzed Oxygenation Mechanisms; Oxidative Organic Chemistry Reactions